REPRODUKSI KETIDAKSETARAAN SOSIAL MELALUI STRUKTUR KOMPETISI OLAHRAGA PADA PERSPEKTIF SOSIOLOGI - Rival Ferryanzah; Mardinata E.M Siburian; Rinaldi; Ibnu luthfi; Nurkadri (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
Social inequality permeates various aspects of human life, with sports competition serving as a significant arena for the reproduction of such disparities. This research explores the dynamics of social inequality reproduction through the lens of sociological perspectives in the context of sports competition. The background highlights the prevalence of social disparities and their impact on the structure of sports competitions. The study aims to understand the mechanisms through which social inequality is perpetuated within the sports domain. The research employs a qualitative sociological approach, utilizing interviews, observations, and analysis of sports competitions to gather data. Findings indicate that existing social structures heavily influence access, opportunities, and success in sports, creating a cycle of inequality reproduction. The competition structure acts as a mirror reflecting broader social disparities, further reinforcing social divisions.